Effet de l’utilisation d’un mélange d’huiles essentielles de romarin et de thym sur l’amélioration de la conservation d’un fromage à caillé lactique - AISSAOUI, louiza (My University, 2019)
This work focused on the study of the effect of the incorporation of essential oils obtained from the two aromatic plant species: Rosemary cineole (Rosmarinus officinalis, leaves) and Thym Thymol (Thymus vulgaris, leaves) on the quality a fresh cheese with lactic curd. It was defined in our experimental protocol the incorporation on our milk cheese curds doses of essential oils selected at concentrations ranging from 0.25 ml / kg to 1ml / kg during the molding-conditioning. Their behavior during the conservation and semi-ripening was determined by monitoring the evolution of physicochemical and microbiological parameters for three weeks at 15 ° C. Our results gave against the control an almost complete inhibition of the flora of deterioration especially for the preparation made with the essential oil of Rosemary which has a broad spectrum fungicidal against the fungal flora compared to that made with the essential oil This alteration flora was initially brought back by the fast-multiplying raw material on the fermented products. The cheese made from 1 ml / kg Thymus HE and with selected initial microbiota of mesophilic strains composed mainly of Lactococcus showed an appreciable organoleptic quality without any alteration of the sensory quality.
Keywords: Essential oils; Rosemary cineole; Thym thymole; inhibition; fungicide